The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fnut.2022.977813
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stability and elemental analysis of sunflower (Helianthus annuus) edible oil produced in Brazil using a domestic extraction machine

Abstract: The consumption of regular vegetable oils has been linked to energy acquisition, nutritional benefits, health improvement, and the regulation of metabolic diseases. This study evaluated fatty acids composition, physicochemical, thermal, oxidative, and optical properties, and quantified trace elements in the sunflower oil extracted by a domestic cold-press machine. The oil presented linoleic (54.00%) and oleic (37.29%) primary unsaturated fatty acids (91.67%), in which atherogenic (0.05), thrombogenic (0.16), h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
0
0
Order By: Relevance
“…The spectra were analyzed according to two wavelengths specific to lipids: 1748 cm −1 for the C=O carbonyl group of unsaturated acids, and 1164 cm −1 (resonance band) with two harmonic bands at 1100 cm −1 and 1296 cm −1 , which are specific for the group C-O. It was established that, practically speaking, the intensity of the light absorption bands at these wavelengths does not vary, regardless of the extraction time, and that they correspond to the bibliographic data for sunflower oil [45]. In the 3100-2800 cm −1 region, C-H valence oscillations were recorded for the saturated carbon atoms, namely, CH 3 -2988 cm −1 and CH 2 -2852 cm −1 , the aliphatic groups from the alkyl residue of triglycerides found in large quantities in vegetable oils.…”
Section: Influence Of Temperature On Physicochemical Parameters and C...mentioning
confidence: 70%
See 1 more Smart Citation
“…The spectra were analyzed according to two wavelengths specific to lipids: 1748 cm −1 for the C=O carbonyl group of unsaturated acids, and 1164 cm −1 (resonance band) with two harmonic bands at 1100 cm −1 and 1296 cm −1 , which are specific for the group C-O. It was established that, practically speaking, the intensity of the light absorption bands at these wavelengths does not vary, regardless of the extraction time, and that they correspond to the bibliographic data for sunflower oil [45]. In the 3100-2800 cm −1 region, C-H valence oscillations were recorded for the saturated carbon atoms, namely, CH 3 -2988 cm −1 and CH 2 -2852 cm −1 , the aliphatic groups from the alkyl residue of triglycerides found in large quantities in vegetable oils.…”
Section: Influence Of Temperature On Physicochemical Parameters and C...mentioning
confidence: 70%
“…In sunflower oil, which is rich in polyunsaturated acids, the degradation of carotenoids increases due to the faster oxidation of unsaturated lipids, which produce radicals that are likely to attack carotenoids [45]. It was found that when the extraction temperature increased from 45 to 65 • C, the individual content of the carotenoids in the sea buckthorn extract decreased from 8.45 mg/100 g DW to 7.47 mg/100 g DW (β-carotene), from 9.40 mg/100 g DW to 8.31 mg/100 g DW (lycopene), from 9.55 mg/100 g DW to 8.44 mg/100 g DW (zeaxanthin), from 8.87 mg/100 g DW to 7.80 mg/100 g DW (βcryptoxanthin), and from 7.76 mg/100 g DW to 6.84 mg/100 g DW, respectively (lutein).…”
Section: Influence Of Temperature On Physicochemical Parameters and C...mentioning
confidence: 99%
“…From this point of view, the oxidative stability of oils is an important indicator of their acceptable shelf life. Different sunflower oil values are given in the literature, probably influenced by their fatty acid composition [26,27]. As can be seen, different additions to RSO affect its value, with additions of rosemary and truffle oil significantly increasing it, while other additions decrease it, most significantly with the addition of linseed oil.…”
Section: Resultsmentioning
confidence: 99%